The perceptions of the parents of children who are victims of negligence and abuse in Turkey regarding the concept of maltreatment - Tunca Güçlü, Nihal; Alkın Şahin, Senar; Körpe, Elif (Southeast Asia Early Childhood Journal, 2022)
In this study, it is aimed to determine the maltreatment behaviors of parents and the emotional outputs of these behaviors. The study is a qualitative research in the phenomenology pattern. In the research, extreme and deviant sampling, one of the purposive sampling methods, was used to determine the participants. The participants of the study are 14 parents of children who are victims of neglect and abuse and who receive service from the Ministry of Family and Social Services. Research data were collected by semi-structured interview technique. Participants were asked 12 demographic questions to get to know them and 25 questions to determine their training needs in order to specify the need for a training program for the protection of children's rights and the prevention of violence against children. The data obtained from the semi-structured interviews were analyzed by inductive analysis. Findings obtained from the parents of children who are the victims of neglect and abuse and who receive service from the Ministry of Family and Social Services reveal that maltreatment is conceptualized as "the situations applied, the reasons for its application, the forms of application, the feelings felt when it is applied". In the study, the fact that parents abuse their children to protect and discipline their children from the outside world indicates that they are ignorant and unconscious in this regard. Families are aware of the negative effects of their ill-treatment on both themselves and their children. This study emphasizes the importance of helping parents gain a deeper understanding, awareness and attitude in preventing child negligence and abuse.